The DnaA Cycle in Escherichia coli: Activation, Function and Inactivation of the Initiator Protein - Katayama, Tsutomu; Kasho, Kazutoshi; Kawakami, Hironori (Frontiers in Microbiology, 2017)
This Review summarizes the mechanisms of the initiator protein DnaA in replication initiation and its regulation in Escherichia coli. The chromosomal origin (oriC) DNA is unwound by the replication initiation complex to allow loading of DnaB helicases and replisome formation. The initiation complex consists of the DnaA protein, DnaA-initiator-associating protein DiaA, integration host factor (IHF), and oriC, which contains a duplex-unwinding element (DUE) and a DnaA-oligomerization region (DOR) containing DnaA-binding sites (DnaA boxes) and a single IHF binding site that induces sharp DNA bending. DiaA binds to DnaA and stimulates DnaA assembly at the DOR. DnaA binds tightly to ATP and ADP. ATP-DnaA constructs functionally different sub-complexes at DOR, and the DUE-proximal DnaA sub-complex contains IHF and promotes DUE unwinding. The first part of this Review presents the structures and mechanisms of oriC-DnaA complexes involved in the regulation of replication initiation. During the cell cycle, the level of ATP-DnaA level, the active form for initiation, is strictly regulated by multiple systems, resulting in timely replication initiation. After initiation, regulatory inactivation of DnaA (RIDA) intervenes to reduce ATP-DnaA level by hydrolyzing the DnaA-bound ATP to ADP to yield ADP-DnaA, the inactive form. RIDA involves the binding of the DNA polymerase clamp on newly synthesized DNA to the DnaA-inactivator Hda protein. In datA-dependent DnaA-ATP hydrolysis (DDAH), binding of IHF at the chromosomal locus datA, which contains a cluster of DnaA boxes, results in further hydrolysis of DnaA-bound ATP. SeqA protein inhibits untimely initiation at oriC by binding to newly synthesized oriC DNA and represses dnaA transcription in a cell cycle dependent manner. To reinitiate DNA replication, ADP-DnaA forms oligomers at DnaA-reactivating sequences (DARS1 and DARS2), resulting in the dissociation of ADP and the release of nucleotide-free apo-DnaA, which then binds ATP to regenerate ATP-DnaA. In vivo, DARS2 plays an important role in this process and its activation is regulated by timely binding of IHF to DARS2 in the cell cycle. Chromosomal locations of DARS sites are optimized for the strict regulation for timely replication initiation. The last part of this Review describes how DDAH and DARS regulate DnaA activity.